Microwave sintered of 10Hydroxyapatite-Yttria stabilized Zirconia-Alumina Bioceramics Composites for biomedical applications - Nur Liyana, Mohd Rosli (Universiti Malaysia Perlis (UniMAP), 2015)
Master of Science in Manufacturing Engineering